Corruption and Inflation Tax in the Middle East and North Africa (MENA) Region: Sensitivity to Definition of Corruption - Samimi, Ahmad Jafari (Journal of Social and Development Sciences, 2011)
Corruption usually harms all aspects of macroeconomic performances of all countries around the World especially the developing world. The purpose of the present paper is to investigate the impact of corruption on inflation tax in MENA countries. In a previous paper1, we used Corruption Perception Index (CPI) as a definition of corruption and applied Friedman, International Bank and Vito Tanzi definitions for inflation tax. We concluded that, there is a positive and significant relationship between corruption and inflation tax. In this paper, we used two different indices for corruption; Corruption Perception Index (CPI) and Control of Corruption Index (CCI) to investigate the sensitivity to different definition of corruption. To do so, we have concentrated on a sample of 17 developing countries from Middle East and North Africa countries for which the necessary data were available for the period 2003-2008. We have used two different indices for corruption; Corruption Perception Index (CPI) and Control of Corruption Index (CCI). Our findings based on panel data (we used unbalanced panel data because of missing data) regression models indicate that in general a positive relationship between corruption and inflation tax exists. In other words, the higher is the corruption the higher will be the inflation tax. Therefore, according to the results, governments have to try to use policies reducing corruption.